Culture Trumps Scientific Fact: ‘Race’ in US American Language - Agwuele, Augustine (Social analysis, 2016)
Once described as humankind’s most dangerous myth, ‘race’ remains a most contentious concept: it is defined one way but used in another. This article examines the use of the term ‘race’ in the utterances of American opinion leaders (scholars and the judiciary, executive, and media) and employs it to explore the dissonance between substantiated knowledge and cultural impositions and the manner in which customary norms outperform scientific facts in everyday interactions. Arguing that the use of the word ‘race’ by opinion leaders furthers its socio-culturally assumed connotations and excites associated emotions and worldviews, the article asks if the change in behavior expected from learning ever occurs in social matters and what the responsibilities of (American) elites are in providing purposeful leadership toward a just and fair society.